(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article aims to discuss how the capitalist system is tensioned through the pedagogical traces contained in the epic methodology of the play Saint Joan of the Stockyards (1929-1931), by the German playwright Bertolt Brecht. The concept of “capitalist seesaw” finds inspiration in the words of the protagonist Joan Dark. However, more than criticizing a system in which, for a few to be at the top, many need to be at the bottom, Brecht contributes to the formation of subject-objects of history, who form their own reflections on their experience with theater and come across a pedagogical poetics that intervenes and leaves traces in politics, economics and education.